Effect of surface treatments on flexural strength properties of ready-made garment waste-reinforced polymer composites - (:unkn) unknown (Fiber Society, 2014)
In this study ready-made garment waste cotton fiber were treated with NaOH and acetic acid then mixed with ready-made garment waste polyamide fiber and polymer composites were produced from these treated cotton/polyamide blend fibers by using thermoset polyester resin as matrix. Then flexural properties of the treated cotton/polyamide waste fiber blend thermoset polyester composites were investigated.
Keywords: Composite; Flexural; Polyamide; Polyester resin; Surface treatment; Textile waste